A industrialização e o desenvolvimento local: parque industrial "Eduardo Dágios" em Pato Branco - PR - Lustosa, Cesar Augusto (2010)
The relationship between global and local should be seen in a dialectical perspective, in which neither the whole can be decomposed or divided into parts, neither the sum of its parts reconstitutes the whole, and therefore they are not divided or self organized. In this perspective the theoretical conceptions and experiences focused on planning, isolated regions. The processes of globalization and technological and structural changes have changed the nature and conditions of local development. The locales should be seen as active spaces with culture, history, human and material resources. In this perspective the innovation and institutional stand formats as central elements, both for understanding as for local development policies. To this end we use mainly the references from Sandra Lencioni, Clério Campolina, Eduardo Gonçalves and Ester Limonad among others we search for a thorough interviewing owners and/or managers of industrial units of industrial park "Eduardo Dágios s" employees etc., to information and data about the thematic studied. This dissertation have reviewed: 1) industrial diversity in the State of Paraná, analyzing the formations of industrial parks and because of this a new territorialization of industry in the State and finally a study on the industry in the region of southwestern Paraná; 2) we see the historical formation of industry in Pato Branco until the formation of the industrial park "Eduardo Dágios"; 3) observe the importance that the bairro Planalto has for some people while dwelling place, leisure entertainment and everyday relations; 4) we see the process of industrialization and local development, having as consequence of the increased quality of life promoted by government agencies and industries, by the way the General infrastructure of the bairro Planalto from the creation of the industrial park "Eduardo Dágios".